2018
DOI: 10.3390/soils2010009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Moisture Status on Soil Cadmium Phytoavailability and Accumulation in Plantain (Plantago lanceolata)

Abstract: The effect of fluctuating soil moisture cycles on soil cadmium (Cd) phytoavailability was investigated in a pot trial with two contrasting soils (Kereone (Allophanic), total Cd 0.79 mg kg −1 ; and Topehaehae (Gley), total Cd 0.61 mg kg −1) that were either sown with plantain (Plantago lanceolata) or left unseeded. Varying soil moisture contents were established using contrasting irrigation regimes: "flooded" (3 days flooded and then 11 days drained); or "non-flooded" (irrigation to 70% of potted field capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…An increase in concentrations of Fe and Mn were found in the soil pore water during flooding, comparable to the increases reported in studies across a range of soil types (Amarawansha et al, 2015;Du Laing et al, 2007;Indraratne and Kumaragamage, 2017;Stafford et al, 2018). It was found that the increase in concentration was much higher for Mn than for Fe, as was also found by Indraratne and Kumaragemage (2017).…”
Section: Reductive Dissolution (Fe/mn)supporting
confidence: 86%
“…An increase in concentrations of Fe and Mn were found in the soil pore water during flooding, comparable to the increases reported in studies across a range of soil types (Amarawansha et al, 2015;Du Laing et al, 2007;Indraratne and Kumaragamage, 2017;Stafford et al, 2018). It was found that the increase in concentration was much higher for Mn than for Fe, as was also found by Indraratne and Kumaragemage (2017).…”
Section: Reductive Dissolution (Fe/mn)supporting
confidence: 86%
“…Remobilisation of PTEs from sediments into the overlying water column during a flooding event depends on the flood regime; the frequency of these intense floods which flush or remobilise contaminated material as well as the duration or alternation of flood with dry spells (Arnell et al, 2015;Foulds et al, 2014;González-Alcaraz and van Gestel, 2015). Whilst research has suggested that the longer the flood duration, the greater the metal mobility (Shaheen et al, 2014a(Shaheen et al, , 2014b, Stafford et al (2018) suggest that even short periods of soil saturation can have an influence the solubility of PTEs.…”
Section: Influence Of Flooding On Ptes Mobilitymentioning
confidence: 99%
“…As, Cd, Cu, Ni, Pb, and Zn), releasing them from the solid phase to pore waters, depending on flood duration (Abgottspon et al, 2015;Ciszewski and Grygar, 2016;Du Laing et al, 2009;Frohne et al, 2011;Karimian et al, 2017;Rinklebe and Du Laing, 2011;Schulz-Zunkel et al, 2015;Shaheen et al, 2016Shaheen et al, , 2014bVaughan et al, 2009). Redox processes are a key factor for the reductive dissolution of Mn and Fe (hydr)oxides, these processes are often catalysed by microorganisms and result in the release of PTEs from the sediment (Du Laing et al, 2009;Frohne et al, 2011;Stafford et al, 2018;Yang et al, 2015). Relatively insoluble Fe(III) and Mn(IV) prevail under aerobic soil conditions providing sorption surfaces for many metals, whereas under anaerobic conditions Mn(IV) and Fe(III) are reduced to more soluble forms (Mn(II) and Fe(II)) with consequential dissolution of Mn and Fe hydrous oxides, cosorbed PTEs ions (e.g.…”
Section: Redox Potential (Eh)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such mild and temporarily reducing conditions have the potential to influence solubility of Cd; Cd will be released if was sorbed to Fe and Mn hydrous oxides and dissolution occurs (Kim and Fergusson, 1992; Backes et al, 1995; Gray et al, 1999b; Loganathan et al, 2012). Other research tested the effects of different irrigation treatments (flooded for 3 d vs. not flooded) on extractable soil Cd concentrations and found no significant effect of these irrigation treatments on extractable soil Cd concentrations or on the soil pH within the same soil type, suggesting that soil Cd is insensitive to short‐term periods of soil saturation (Stafford et al, 2018). …”
Section: Discussionmentioning
confidence: 99%